Pengaruh Harga Dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan Dan Dampaknya Terhadap Citra PT. Sucofindo - Haryono, Haryono; R. Dwi Sunu Kanto (Dinasti Review, 2024)
The high level of competition and the increasingly advanced era requires companies to be more innovative in adapting to changes that have occurred. The ups and downs of the company often occur along with changes in environmental conditions around it. In addition, the influence of government regulations can also affect the dynamics of competition in these sectors. With the implementation of good service quality, it is hoped that customer satisfaction will be achieved which will certainly have an impact on the development of PT Sucofindo in the future. The objectives of this study are: (1) To determine the effect of price on customer satisfaction in using PT Sucofindo's services. (2) To determine the effect of service quality on customer satisfaction in using PT Sucofindo's services. (3) To determine the effect of price on the brand image of PT Sucofindo's services. (4) To determine the effect of service quality on the brand image of PT Sucofindo. (5) To determine the effect of customer satisfaction on the brand image of PT Sucofindo. (6) To determine the mediation of customer satisfaction on the effect of price on the brand image of PT Sucofindo. (7) To determine the mediation of customer satisfaction on the effect of service quality on the brand image of PT Sucofindo. In this study, data processing and analysis used the Partial Least Square (PLS) approach. PLS is a Structural Equation Modeling (SEM) model based on components or variants. While PLS is more of a predictive model. Data analysis in this study is Outer Model Analysis, Inner Model, and Hypothesis Testing. Based on the results of the analysis, it shows that: (1) Price does not affect Customer Satisfaction; (2) Service Quality affects Customer Satisfaction; (3) Price affects Brand Image; (4) Service Quality affects Brand Image; (5) Customer Satisfaction affects Brand Image; (6) Mediating customer satisfaction on the influence of price on brand image has no effect; and (7) Mediating customer satisfaction on the influence of price on brand image has an effect. It can be concluded that the variables of Service Quality and Customer Satisfaction affect the brand image of PT. Sucofindo.